2022
DOI: 10.1371/journal.pone.0272439
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and emergency department presentation after hospitalisation for epilepsy in people with intellectual disability: A data linkage study

Abstract: Background Despite the high prevalence of epilepsy and multiple barriers to care in people with intellectual disability, the risk of returning to hospital after an admission for epilepsy is largely unknown. In this study, we sought to quantify and compare readmission and emergency department (ED) presentations after hospitalisation for epilepsy in people with and without intellectual disability. Methods and findings Using linked administrative datasets, we conducted a retrospective cohort study of people age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The effect of intentional self-harm on readmission risk observed in people with epilepsy and ID may be explained by many factors, including underlying psychiatric conditions. While a high risk of self-harm may have contributed to more readmissions (Owens et al 2002), the evidence indicates that self-harm likely accounted for less than 9% of readmissions and even fewer in children (Liao et al 2022). Our finding emphasises the need for more research to improve recognition and potentially also the management of intentional self-harm in people with ID and epilepsy.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The effect of intentional self-harm on readmission risk observed in people with epilepsy and ID may be explained by many factors, including underlying psychiatric conditions. While a high risk of self-harm may have contributed to more readmissions (Owens et al 2002), the evidence indicates that self-harm likely accounted for less than 9% of readmissions and even fewer in children (Liao et al 2022). Our finding emphasises the need for more research to improve recognition and potentially also the management of intentional self-harm in people with ID and epilepsy.…”
Section: Discussionmentioning
confidence: 69%
“…People with more severe and refractory epilepsy could have more readmissions for epilepsy. Epilepsy is the leading reason for readmission within both 30 and 365 days after hospitalisation for epilepsy in both children and adults with ID (Liao et al 2022), and other prevalent reasons include respiratory, mental and infectious diseases and injuries. Among the broader population of people with ID (including individuals both with and without epilepsy), research has also repeatedly observed the association of greater comorbidity burden with more frequent hospitalisation or re-hospitalisation (Balogh et al 2013;Sheehan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates substantially higher costs of mental health care for people with intellectual disability, and inefficiency of this care through frequent re-presentations to acute care services after discharge'. 28 Increased efficiencies in Elrod and Fortenberry's framework are gained through the centralization of specialist technologies, skills and services at the hub. Centralization increases efficiencies by eliminating duplication of services, offering increased return on investment and bolstering economies of scale.…”
Section: Increased Efficienciesmentioning
confidence: 99%